Nizek površinski stanovanjski standard v Sloveniji - Sendi, Richard (Urbani izziv, 2013)
This article advances and argues the thesis that Slovenia has a low housing standard and that the majority of people live in dwellings that may be described as overcrowded according to internationally recognised standards. Evidence supporting this thesis is provided with the help of statistical data,a comprehensive literature review and a review of the views of various Slovenian authors that have discussed the subject in the past. In addition to an extensive review of domestic and foreign literature, I also highlight the major historical factors that have significantly influenced the implementation and maintenance of the current housing standard. The final part of the article identifies and discusses a widely held false conviction that I characterise as the major obstruction to the introduction of a higher housing standard in Slovenia. In this section, I suggest alternative theoretical explanations for the continued maintenance of the low housing standard. The final aim of the article is to spur concrete actions that will lead to implementing appropriate measures and eventual improvement of the housing standard.
Keywords: ekonomika; kupna moč; Slovenija; stanovanja; stanovanjska politika; življenjski standard